2018
DOI: 10.1111/jfpp.13654
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of red onion peel polyphenols fractions by freeze drying technicality and its application in cake

Abstract: This work focuses on extraction of biological compounds from red onion peels and its microencapsulation using maltodextrin (MD), soybean protein isolate, and a complex of soybean protein isolate (SPI) and maltodextrin by freeze drying manner. Furthermore, there was a quality evaluation for cake integrated with microencapsulated polyphenols as well as polyphenols stability assessment after baking. Extracts of red onion peel were produced by three methanol concentrations (50, 75, or 100% v/v). A 75% methanolic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In this study, the microcapsule coated with GA:WPI of 3:7 had the lowest moisture content and highest thermal stability, which can play an important role in the chemical stability of CH in microcapsules and can show better antioxidation activity as compared to other microcapsules coated with ratio of GA:WPI. These results were in agreement with previous studies which showed that the suitable carbohydrate and protein ratio of wall materials can present good antioxidant activity [ 46 , 47 ].…”
Section: Resultssupporting
confidence: 93%
“…In this study, the microcapsule coated with GA:WPI of 3:7 had the lowest moisture content and highest thermal stability, which can play an important role in the chemical stability of CH in microcapsules and can show better antioxidation activity as compared to other microcapsules coated with ratio of GA:WPI. These results were in agreement with previous studies which showed that the suitable carbohydrate and protein ratio of wall materials can present good antioxidant activity [ 46 , 47 ].…”
Section: Resultssupporting
confidence: 93%
“…Our reported data are in agreement with other studies. Elsebaie & Essa (2018) reported a high EE of 94.30 ± 1.50 % of ROS extract in SPI and maltodextrin. Additionally, Tao et al (2017) combined various shell materials (whey proteins, gum Arabic, maltodextrin, and β-cyclodextrin) for the encapsulation of blueberry extracts and reported anthocyanins’ EE with values exceeding 82 %.…”
Section: Resultsmentioning
confidence: 96%
“…HPLC analysis of barnûf leaves extract (BLE) was performed in the Laboratory of Food Chemistry, Institute of Food Technology Research, National Research Center, Egypt. The quantitative measurement of BLE phenolics content was conducted via the protocol outlined via Elsebaie and Essa (2018) utilizing HPLC instruments (Shimadzu LC-10A; Kyoto; Japan).…”
Section: Hplc Analysismentioning
confidence: 99%